Polar Liquid Crystal Elastomers Cross Linked Far from Thermodynamic Phase Transitions: Dislocation Loops in Smectic Clusters - Yusril Yusuf; Shohei Yamaguchi; Shinya Kawano; Hirotaka Okabe; Simon Krause; Heino Finkelmann; P. E. Cladis; Shoichi Kai (Advances in Condensed Matter Physics)
Nematic networks with three different concentrations of polar and nonpolar mesogens and the same concentration of a novel cross-linking agent give rise to unusual liquid single crystal elastomers (LSCEs) that are transparent monodomain nematic networks with smectic clusters. The largest spontaneous length change is observed in the sample with 70 mol% of the polar mesogen which also has the highest glass transition temperature and smectic clusters with a slowly increasing but nearly constant layer spacing on cooling from 90°C to 25°C. X-ray scattering intensity from smectic clusters with layer spacings that monotonically increase on cooling first increases to a maximum at T*~60∘C corresponding to clusters of about 30 layers. Below T∗, the scattering intensity decreases as the number of layers in a cluster decreases. To account for this surprising nonlinear behavior that correlates with nonlinear features of the networks’ macroscopic spontaneous shape change and birefringence, a model is proposed where dislocations form in the layers at T∗. Below T∗, more dislocations form to break down the layer structure. The possibility of dislocation formation at T∗ independent of mesogenic concentrations is attributed to a conformational change in the crosslinker which is present at the same concentration in the three LSCEs.